Production of Sc medical radioisotopes with proton and deuteron beams. (December 2018) - Sitarz, Mateusz; Szkliniarz, Katarzyna; Jastrzębski, Jerzy; Choiński, Jarosław; Guertin, Arnaud; Haddad, Ferid; Jakubowski, Andrzej; Kapinos, Kamil; Kisieliński, Maciej; Majkowska, Agnieszka; Nigron, Etienne; Rostampour, Malihe; et al.
Abstract: Proton and deuteron beams (15.3 and 6.8 MeV, respectively) extracted from the PETtrace medical cyclotron at the Radiopharmaceuticals Production and Research Centre in the University of Warsaw, Heavy Ion Laboratory, 28 MeV protons from the C30 cyclotron at the National Centre for Nuclear Research, Świerk, near Warsaw and 33 MeV protons from the ARRONAX accelerator, Nantes were used to produce and investigate the medically interesting Sc radioisotopes. Both natural and isotopically enriched CaCO3 and TiO2 targets were used ( 42 Ca, 43 Ca, 44 Ca, 48 Ca, 48 Ti). The production efficiency and isotopic purity were determined and are reported here for the highest commercially available enrichments of the target material. The Thick Target Yield, Activities at the End of Bombardment (EOB) and the relative activities of produced impurities at EOB are reported for 43 Sc, 44g Sc, 44m Sc and 47 Sc produced with particle energies below 33 MeV. Highlights: The prospective medical scandium radioisotopes, 43 Sc, 44g Sc, 44m Sc and 47 Sc were produced using proton and deuteron beams. Isotopically enriched and natural targets of CaCO3 and TiO2 were used. The Thick Target Yields and radioactive impurities were determined for proton energy up to 28 MeV and deuteron up to 7 MeV. TTY for 43Sc, 44gSc and 47Sc production with proton beam and enriched targets reached about 400, 1000 and 100 MBq/µAh.